2000
DOI: 10.1007/s004210050660
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the renin-angiotensin system and athletic performance

Abstract: The D allele at the angiotensin-I-converting enzyme (ACE)-insertion/deletion polymorphism has been associated with an increased risk of developing several pathological processes, such as coronary heart disease and ventricular hypertrophy. Individuals with the DD genotype show a significantly increased left-ventricular mass in response to physical training, compared to the II genotype (which would be associated with the lowest plasma ACE levels) and the ID genotype. The II genotype has been linked to a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
97
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(111 citation statements)
references
References 18 publications
6
97
2
6
Order By: Relevance
“…The study have supported the interpretation concerned ACE activity is Montgomery research On the other hand, in spite of many positive association studies suggests that there is an influence of ACE genotype on athletic performance, there are also the studies have found no evidence for association described above [14,19]. Also the Nazarov [12] This conclusion seems to be confirmed by studies by Alvarez carried out on handball players [1]. Unfortunately, it is difficult to verify this hypothesis due to the insufficient number of surveys on the significance of genetic conditions in fighting sports (ACE gene has been examined only once in the context of judo, in a paper by Oh [13] but with no clear conclusions).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The study have supported the interpretation concerned ACE activity is Montgomery research On the other hand, in spite of many positive association studies suggests that there is an influence of ACE genotype on athletic performance, there are also the studies have found no evidence for association described above [14,19]. Also the Nazarov [12] This conclusion seems to be confirmed by studies by Alvarez carried out on handball players [1]. Unfortunately, it is difficult to verify this hypothesis due to the insufficient number of surveys on the significance of genetic conditions in fighting sports (ACE gene has been examined only once in the context of judo, in a paper by Oh [13] but with no clear conclusions).…”
Section: Discussionsupporting
confidence: 51%
“…Analyses show that allele D is related to an increase in the strength of the quadricipital thigh muscle in a response to a nine-week isometric-strength training [5]. These facts may be a proof the ACE D allele has been associated with higher ACE activity, compared to the ACE I allele [1,6]. The study have supported the interpretation concerned ACE activity is Montgomery research On the other hand, in spite of many positive association studies suggests that there is an influence of ACE genotype on athletic performance, there are also the studies have found no evidence for association described above [14,19].…”
Section: Discussionmentioning
confidence: 94%
“…4 The insertion (I) allele turned out to be over-represented among high-altitude mountaineers 4 and carriership of at least one I allele was associated with improved endurance among males recruited in the UK army. 4 Among elite endurance athletes, a significantly higher frequency of the I allele was reported in 64 Australian rowers, 5 79 British Olympic-standard runners selected as potential Olympic competitors 6 and 60 Spanish athletes, 7 as compared with controls. Conversely, an excess of the deletion (D) allele has been reported among elite athletes competing in more power-oriented sports such as short distance swimming 6,8 and sprinting.…”
mentioning
confidence: 99%
“…Differences in genotypes in the same population according to ethnic-ity have also been described (Foy et al, 1997;Akbulut et al, 2004;Zhang et al, 2010). ACE activity is higher in subjects with the DD genotype (Alvarez et al, 2000;Elshamaa et al, 2011). The ACE genotype also affects the pathologies of the vascular endothelial tissue (Johnston, 1994;Morishita et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…ACE gene polymorphisms play a role in the disease (Dzielińska et al, 2011;Pandey et al, 2011). Further, the ACE I/D polymorphism has been examined as a risk factor for CAD, MI, cardiomyopathies, and sudden cardiac death, among others (Marian et al, 1993;Alvarez et al, 2000). The frequency of the D allele of ACE (I/D) differs among populations (Tokgözoğlu et al, 1997;Oren et al, 1999).…”
Section: Discussionmentioning
confidence: 99%